Case report: Intrapleural plus systemic Tislelizumab injection combined chemotherapy in RET gene fusion-positive lung adenocarcinoma presenting refractory malignant pleural effusion - Qiu, Dong; Zhang, Xiao-Hui; Wang, Yang; Chen, Cheng (Frontiers in Oncology, 2024)
RET fusions were discovered in non-small cell lung cancer (NSCLC), and the efficacy of RET-targeted treatment in these patients has been previously established. However, patients with required resistance to RET-TKIs have limited treatment options. Herein, we describe a case of critical and advanced lung adenocarcinoma harboring RET fusion. Despite a significant response to Prasetinib previously, the patient developed refractory malignant pleural effusion after 24 months of treatment. He was treated simultaneously with intrapleural plus systemic Tislelizumab injection combined chemotherapy, thereby achieving an excellent clinical benefit maintaining control of pleural effusion for over 6 months. Hence, we would like to discuss intrapleural immunotherapy as an additional treatment method in refractory malignant pleural effusion while demonstrating good treatment tolerance.